A Coplanar Vivaldi Antenna Design with Improved Frequency Response for Microwave Breast Imaging - Uyanik, Cafer; Ertay, Agah Oktay; Dogu, Semih; Akduman, Ibrahim; Sahinturk, Hulya (IEEE, 2016)
The main goal of this work is to present a planar director added coplanar Vivaldi antenna with improved impedance bandwidth, directivity for microwave breast imaging applications. Three stage design procedure is proposed to enhance the directivity and impedance bandwidth. Proposed antenna operates from 1.3GHz to 7.09GHz which fractional bandwidth is over 138%. The directivity of the proposed antenna is relatively enhanced at higher frequencies. The designed antenna structure has 64x70x1.6 mm(3) dimensions and suitable for microwave imaging applications.
Keywords: Engineering; Telecommunications